Pengaruh Situasi Sosial Dan Nilai Budaya Madura Terhadap Regulasi Emosi Individu Etnis Madura - Setyaningsih Setyaningsih (Universitas Trunojoyo Madura, 2021)
AbstrakAll this time individual of Madurese ethnic are known temperamental and emotional as well as highly carry self esteem. Social situation and the Madurese cultural values take role in emotion regulation. This research is intended to see and to test of the influence of Madurese social situation and cultural values toward their emotion regulation. This research uses 400 persons as samples taken from 4 (four) regencies available in Madura island by applying Multi stage sampling technique. The data are taken by using the emotion regulation scale, social situation scale and the Madurese cultural value scale. All of these samples are analysed by using the Partial Least Square (PLS) Methode. Output of calculation indicates Madurese cultural values greater impact on emotion regulation compared with social situation. Key word : social situation, Madurese cultural values, emotion regulation. Abstrak Selama ini individu etnis Madura diketahui temperamental dan emosional serta menjunjung tinggi harga diri. Situasi social dan nilai budaya Madura berperan terhadap regulasi emosi. Penelitian ini bertujuan untuk melihat dan menguji pengaruh dari situasi social dan nilai budaya Madura terhadap regulasi emosi individunya. Penelitian ini menggunakan sampel 400 orang dari empat kabupaten yang ada di Pulau Madura, dengan teknik multistage sampling. Data digali menggunakan skala regulasi emosi, situasi social, skala nilai budaya Madura dan dianalisis dengan menggunakan Partial Least Square (PLS). Hasil perhitungan menunjukkan nilai budaya Madura lebih besar pengaruhnya terhadap regulasi emosi disbanding dengan situasi sosial. Kata kunci : situasi sosial, nilai budaya Madura, regulasi emosi.